Graphene nanoplatelets (GNPS) exfoliation and dispersion in metal powder using different solvents - Baig, Z. (Asian Research Publishing Network, 2016)
Graphene possesses attractive mechanical and physical properties than available nanomaterials and considered as ideal reinforcement in many metals to enhanced mechanical properties. Incorporation and uniform dispersion of graphene in metals is the ultimate challenge due to difference in surface energies of both contents. Graphene usually available as stacks of multisheets and need exfoliation to obtain single or bi layer because reported unique properties are associated with single layer graphene. In current work, colloidal processing of graphene is employed and processed with iron powder. In this contest exfoliation has been achieved by using different solvents and dispersion attained by mechanically stirred with iron powder at fixed rate. The effect of graphene exfoliation in different solvents and dispersion in iron powder is systematically investigated by FESEM, energy-dispersive X-ray spectroscopy, particle size measurement. To study dispersion effect, hardness and density measurements were conducted on vacuum sintered nanocomposite compacts. Â©2006-2016 Asian Research Publishing Network (ARPN).